Disposition of [14C]hydroquinone in Harlan Sprague-Dawley rats and B6C3F1/N mice: species and route comparison. (2nd November 2018) - Black, Sherry R.; Fennell, Timothy R.; Mathews, James M.; Snyder, Rodney W.; Patel, Purvi R.; Watson, Scott L.; Sutherland, Vicki; Waidyanatha, Suramya
Abstract: 1. Hydroquinone (HQ) is present in some foods and has varied industrial, medical and consumer uses. These studies were undertaken to investigate the disposition of HQ in rats and mice following gavage, intravenous (IV) and dermal exposure. 2. [ 14 C]HQ administered (0.5, 5 or 50 mg/kg) by gavage or IV routes to male and female Harlan Sprague-Dawley (HSD) rats and B6C3F1/N mice was well absorbed and rapidly excreted primarily in urine. Radioactivity remaining in tissues at 72 h was <1% for both species at all dose levels and routes. No sex, species or route related differences in disposition were found. 3. With dermal application of 2, 10 or 20% [ 14 C]HQ, mice absorbed higher percentages of the dose than rats (37, 12, 12% versus 18.6, 4.43 and 1.79%, respectively). The HQ mass absorbed by mice increased with dose, while in rats it was more constant over the dose range. Absorbed HQ was rapidly excreted in urine of both species and urinary excretion indicated continued absorption over the exposure period. No sex differences in disposition were found. 4. The oral bioavailability of HQ at 5 mg/kg was low in both rats (1.6%) and mice (3.9%) demonstrating significant first pass metabolism. Dermal bioavailability in mice was 9.4% following application of 2% formulation. 5. Urinary metabolites for both species and all routes included the glucuronide and sulfate conjugates; no parent was found in urine.